2006
DOI: 10.1016/j.jcis.2005.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Filling kinetics of liquids in nanochannels as narrow as 27 nm by capillary force

Abstract: We report the filling kinetics of different liquids in nanofabricated capillaries with rectangular cross-section by capillary force. Three sets of channels with different geometry were employed for the experiments. The smallest dimension of the channel cross-section was respectively 27, 50, and 73 nm. Ethanol, isopropanol, water and binary mixtures of ethanol and water spontaneously filled nanochannels with inner walls exposing silanol groups. For all the liquids the position of the moving liquid meniscus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 32 publications
6
89
0
1
Order By: Relevance
“…This observation is striking since one might expect that specific interactions of ethanol and water molecules with the SiO x channel walls would affect the dynamics of fluid flow in channels with a thickness of merely 20-50 water molecules. Yet, like in earlier studies of significantly wider nanochannels (from 27 to 73 nm; Han et al 2006) surface effects do not seem to play a major role. Han et al had reported reasonably consistent filling dynamics of 40% ethanol-water mixtures in a 27 nm deep and 900 nm wide nanochannel compared to pure water and ethanol.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This observation is striking since one might expect that specific interactions of ethanol and water molecules with the SiO x channel walls would affect the dynamics of fluid flow in channels with a thickness of merely 20-50 water molecules. Yet, like in earlier studies of significantly wider nanochannels (from 27 to 73 nm; Han et al 2006) surface effects do not seem to play a major role. Han et al had reported reasonably consistent filling dynamics of 40% ethanol-water mixtures in a 27 nm deep and 900 nm wide nanochannel compared to pure water and ethanol.…”
Section: Discussionsupporting
confidence: 63%
“…The general finding of all those experiments is that the filling dynamics of typically pure simple fluids follows the classical Lucas-Washburn law (Lucas 1918;Washburn 1921), in which the meniscus advances proportional to the square root of time. However, in most instances, it was found that the prefactor in that algebraic law was reduced compared to the theoretical expectations, which was attributed to various possible effects including an electrokinetic counter flow (Tas et al 2004) (later disputed by others; Mortensen and Kristensen 2008), the presence of bubbles (Thamdrup et al 2007), elastic deformations of the channel wall, and an increased dynamic contact angle (Han et al 2006). One of the most important problems is that most experiments do not allow for distinguishing between confinement effects arising from a variation of the macroscopic materials properties (viscosity, surface tension) and retarding effects on the moving meniscus, e.g., due to wall roughness, pinning, and slip.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These advances are leading to studies with microfluidic (e.g. Yang et al, 2011) and nanofluidic capillaries widths of a few tens of nm (Han et al, 2006) or with depths as small as 6 nm (Oh et al, 2009). Whilst non-constant channel cross sections have been a focus of study experimentally and theoretically (Legait, 1983;Staples andShaffer, 2002, Reysatt et al, 2008;Liou et al, 2009), increased solid-liquid contact area, and hence increased capillary pull can be achieved using a range of in-channel structures.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for the enhanced concentration of Alexa is the adsorption of Alexa at the liquid-air interface. In the traditional picture, the interface is free of ions, however it was shown recently [40] that larger polarizable ions may have a propensity for the interface. The liquid pockets in our experiment are the results of transport through the channel corners, which involves a large surface-to-volume ratio and therefore can contribute the concentration of species that are adsorbed at the interfaces.…”
Section: Fluorescence Intensity Images Of Fluorescent Molecules Filmentioning
confidence: 99%